Clinical and Epidemiological Features of a Family Cluster of Symptomatic and Asymptomatic Severe Acute Respiratory Syndrome Coronavirus 2 Infection. (22nd May 2020) - Wolf, Gerhard K; Glueck, Thomas; Huebner, Johannes; Muenchhoff, Maximilian; Hoffmann, Dieter; French, Lars E; Keppler, Oliver T; Protzer, Ulrike
Abstract: In a family experiencing coronavirus disease 2019, the parents and 2 children aged 2 and 5 years became infected but the youngest child was not infected. Both children initially shed infectious virus, but cleared the virus after 5 to 6 days in the nasopharynx. However, viral RNA was continuously detected in the children's stool for more than 4 weeks.